Analyse der mechanischen Randbedingungen zur Adaption der oszillierenden Hinterschneidtechnik an einen Mobilbagger - Weidemann, Roman (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2014)
The oscillating disc cutting process has shown excellent results in precisely removing area-limited-concrete structures. Due to the highly dynamic oscillatory motion, the stiffness requirements to the tool structure and the basic machine have to be considered, which is the main purpose of this work. Based on these results, a concept of a mechanical adaption of the oscillating disc cutting process to an excavator attachment tool will be developed and tested on a prototype.